An Analysis on Java Programming Language Decompiler Capabilities - Gusarovs, Konstantins (Applied Computer Systems (Online), 2018)
Along with new artifact development, software engineering also includes other tasks. One of these tasks is the reverse engineering of binary artifacts. This task can be performed by using special “decompiler” software. In the present paper, the author performs a comparison of four different Java programming language decompilers that have been chosen based on both personal experience and results of a software developer survey.